Does fluoride in the water close the dental caries gap between Indigenous and non‐Indigenous children?. (29th July 2015) - Lalloo, R; Jamieson, LM; Ha, D; Ellershaw, A; Luzzi, L
Abstract Background Indigenous children experience significantly more dental caries than non‐Indigenous children. This study assessed if access to fluoride in the water closed the gap in dental caries between Indigenous and non‐Indigenous children. Methods Data from four states and two territories were sourced from the Child Dental Health Survey (CDHS) conducted in 2010. The outcomes were dental caries in the deciduous and permanent dentitions, and the explanatory variables were Indigenous status and access to fluoridated water (≥0.5 mg/L) prior to 2008. Results Dental caries prevalence and severity for Indigenous and non‐Indigenous children, in both dentitions, was lower in fluoridated areas compared to non‐fluoridated areas. Among non‐Indigenous children, there was a 50.9% difference in mean dmft scores in fluoridated (1.70) compared to non‐fluoridated (2.86) areas. The difference between Indigenous children in fluoridated (3.29) compared to non‐fluoridated (4.16) areas was 23.4%. Among non‐Indigenous children there was a 79.7% difference in the mean DMFT scores in fluoridated (0.68) compared to non‐fluoridated (1.58) areas. The difference between Indigenous children in fluoridated (1.59) and non‐fluoridated (2.23) areas was 33.5%. Conclusions Water fluoridation is effective in reducing dental caries, but does not appear to close the gap between non‐Indigenous children and Indigenous children.